The usage of Empty Fruit Bunches (EFB) among smallholders in oil palm plantation at Felda Lepar Hilir 3, Pahang / Samarobitah Abdullah - Abdullah, Samarobitah (Faculty of Plantation and Agrotechnology, 2019)
The oil palm industry has been growing exponentially over the past years that lead to increasing amounts of waste products especially EFB from the oil palm tree. The past study showed that smallholders facing several barriers to use EFB as material in oil palm plantation. The study was carried out to identify the usage of EFB in oil palm plantation. To achieve the objective, a set of data was collected through the questionnaires related to the variables (environment, price, cost, knowledge) in the study. A survey of 137 smallholders was carried out at Felda Lepar Hilir 3, Pahang. The gathered data was analyzed using descriptive, correlation and regression analysis. From correlation analysis, it was identified environment, cost, price and knowledge have positive linear relationship with usage of EFB in oil palm plantation. The relationship between knowledge toward usage of EFB was indicated strong correlation. The environment, price and cost factor was indicated moderate correlation. From regression analysis, 70.5% of variation in usage of EFB was explained by independent variables (price, cost, knowledge) and another 20.5% was explained by other factors. The most influence independent variable towards the usage of EFB in oil palm plantation was cost factor with the highest value (β= 0.431) followed by knowledge (β= 0.353) and price (β= 0.225). As a conclusion, smallholders should use the EFB as a mulching material to conserve water and nutrients in soil that give benefits towards oil palm growth and environmental condition. Government agencies should responsible to instruct smallholders in implementing EFB in oil palm plantation.